Comparative effectiveness of mobocertinib and standard of care in patients with NSCLC with EGFR exon 20 insertion mutations: An indirect comparison. (May 2023) - Ou, Sai-Hong I.; Lin, Huamao M.; Hong, Jin-Liern; Yin, Yu; Jin, Shu; Lin, Jianchang; Mehta, Minal; Zhang, Pingkuan; Nguyen, Danny; Neal, Joel W.
Highlights: Single-arm phase I/II clinical trial in patients with advanced EGFR ex20ins NSCLC. Compared outcomes with mobocertinib vs real-world treatment in this rare population. Confirmed overall response rate was greater with mobocertinib than other treatments. Median PFS (7.3 vs 3.3 months) and OS (24.0 vs 12.4 months) were also greater. Mobocertinib substantially outperformed available therapies in this population. Abstract: Introduction: Mobocertinib is a novel, first-in-class, irreversible, oral epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI) designed to selectively target in-frame EGFR exon 20 insertions (ex20ins). Comparative effectiveness data for mobocertinib versus real-world treatments are lacking in this rare population. This study compared data for mobocertinib reported in a Phase I/II single-arm clinical trial with an external control group consisting of patients who received available treatment in the real-world setting in the United States (US). Materials and Methods: The mobocertinib group included platinum-pretreated patients with advanced EGFR ex20ins non-small cell lung cancer (NSCLC) receiving mobocertinib 160 mg QD in an ongoing, single-arm, phase 1/2 clinical trial (NCT02716116; n = 114). The real-world data (RWD) group included platinum-pretreated patients with advanced EGFR ex20ins-mutant NSCLC from the Flatiron Health database (n = 50). Inverse probability treatment weighting based on the propensity score method controlled for potential confounding between groups. Confirmed overall response rate (cORR), progression-free survival (PFS), and overall survival (OS) were compared between groups. Results: After weighting, baseline characteristics were balanced. Patients in the RWD group received EGFR TKI (20 %), immuno-oncology therapy (40 %), or any regimens containing chemotherapy (40 %) in the second- or later-line setting. In the mobocertinib and RWD groups, respectively, cORR was 35.1 % and 11.9 % (odds ratio: 3.75 [95 % confidence interval (CI): 2.05, 6.89]); median PFS was 7.3 and 3.3 months (hazard ratio [HR]: 0.57 [95 % CI: 0.36, 0.90]); and median OS was 24.0 and 12.4 months (HR: 0.53 [95 % CI: 0.33, 0.83]) after weighting. Discussion: Mobocertinib showed substantially improved outcomes versus an external control group using available therapies in platinum-pretreated patients with EGFR ex20ins-mutant NSCLC. In the absence of comparative evidence from randomized trials, these findings help elucidate potential benefits of mobocertinib in this rare population.